2023
DOI: 10.3390/w15030428
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Operation of a Pilot-Scale Sulfur-Based Autotrophic Denitrification System for Deep Nitrogen Removal

Abstract: Sulfur-based autotrophic denitrification is a novel biological denitrification process characterized by the absence of an organic carbon source, a short reaction time, a high denitrification rate, a low treatment cost, and a small footprint. However, the technique is facing challenges with respect to engineering applications. In this study, a pilot-scale sulfur-based autotrophic denitrification system was established with an optimal hydraulic retention time (HRT) of 0.21 h, which achieved the highest denitrifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Figure 3d shows that the pH value of this system was always stabilized at 6.5-9 during the reactor operation, which was in the normal growth range of the microorganisms, indicating that steel slag could maintain the pH stabilization of this system [4,30]. As shown in Figure 3e, SO 4 2− increased greatly between outlet 1 and outlet 3, which confirmed that this stage was the best stage for denitrification, which was also confirmed by the TN and NO 3 -N test results [31]. Theoretically, under the condition of the presence of a sufficient electron donor and autotrophic denitrifying bacteria, every 1 g of NO 3…”
Section: Investigation Of Nitrogen Removal Performance For Simulated ...supporting
confidence: 67%
“…Figure 3d shows that the pH value of this system was always stabilized at 6.5-9 during the reactor operation, which was in the normal growth range of the microorganisms, indicating that steel slag could maintain the pH stabilization of this system [4,30]. As shown in Figure 3e, SO 4 2− increased greatly between outlet 1 and outlet 3, which confirmed that this stage was the best stage for denitrification, which was also confirmed by the TN and NO 3 -N test results [31]. Theoretically, under the condition of the presence of a sufficient electron donor and autotrophic denitrifying bacteria, every 1 g of NO 3…”
Section: Investigation Of Nitrogen Removal Performance For Simulated ...supporting
confidence: 67%